Between waves (2020)
After a rigorous analysis of the 7 de Agosto sector and the study of various references, it was decided to implement a reorganization of uses in one of the project's blocks and from there to improve the relations between uses and workers in the sector, without being indifferent to its dynamics. The project does not intend to eliminate any formal or informal activity, but without generating a way in which they can relate in a way in which everyone benefits, especially the workshop workers, who are the economic, social and cultural base of the sector.